Out of Amazonia: Late-Holocene climate change and the Tupi–Guarani trans-continental expansion. (July 2017) - Iriarte, José; Smith, Richard J; Gregorio de Souza, Jonas; Mayle, Francis Edward; Whitney, Bronwen S; Cárdenas, Macarena Lucia; Singarayer, Joy; Carson, John F; Roy, Shovonlal; Valdes, Paul
The late-Holocene expansion of the Tupi–Guarani languages from southern Amazonia to SE South America constitutes one of the largest expansions of any linguistic family in the world, spanning ~4000 km between latitudes 0°S and 35°S at about 2.5k cal. yr BP. However, the underlying reasons for this expansion are a matter of debate. Here, we compare continental-scale palaeoecological, palaeoclimate and archaeological datasets, to examine the role of climate change in facilitating the expansion of this forest-farming culture. Because this expansion lies within the path of the South American Low-Level Jet, the key mechanism for moisture transport across lowland South America, we were able to explore the relationship between climate change, forest expansion and the Tupi–Guarani. Our data synthesis shows broad synchrony between late-Holocene increasing precipitation and southerly expansion of both tropical forest and Guarani archaeological sites – the southernmost branch of the Tupi–Guarani. We conclude that climate change likely facilitated the agricultural expansion of the Guarani forest-farming culture by increasing the area of forested landscape that they could exploit, showing a prime example of ecological opportunism.